Limit Equilibrium Analysis of Slope Reinforcement Under Varying Pore Pressure: A Case Study of Cabean Dam Conduit Channel - Rachman, Muhammad Perwira; Sangkawati, Sri; Sriyana, Ignatius (Fakultas Teknik Universitas Tanjungpura, 2026)
Slope instability induced by rainfall infiltration and increasing pore-water pressure is a common geotechnical problem in tropical regions. This study evaluates the effectiveness of slope-reinforcement methods applied to the conduit channel slope at Cabean Dam, Central Java, Indonesia. Stability analysis was conducted using three limit-equilibrium methods—Ordinary, Bishop Simplified, and Morgenstern–Price—implemented in SLOPE/W. Three slope conditions were analyzed: the original slope configuration, slope flattening combined with soil nail reinforcement, and slope flattening combined with shotcrete treatment. A sensitivity analysis was performed by varying the pore pressure ratio (Ru) from 0.0 to 0.7 to represent different rainfall infiltration conditions. The results indicate that the initial slope condition is unstable, with safety factors below acceptable engineering standards. Soil nail reinforcement significantly improves slope stability but remains sensitive to increasing pore pressure. The combination of slope flattening and shotcrete treatment provides the highest safety factors and the lowest sensitivity to pore-pressure variations, indicating better performance for slope stabilization in high-rainfall environments.